A review of the genus Tuberaleyrodes Takahashi (Hemiptera: Aleyrodidae) with description of five new species from Brunei, Hong Kong and Malaysia - Dubey, Anil Kumar; Martin, Jon H. (Zootaxa, 2018)
The whitefly genus Tuberaleyrodes Takahashi is reviewed using types and determined specimens. The generic diagnosis is redefined together with description of five new species: T. bruneiensis Dubey & Martin sp. nov. from Brunei, T. crypta Dubey & Martin sp. nov. from Hong Kong, and T. ordo Dubey & Martin sp. nov., T. aequalis Dubey & Martin sp. nov. and T. variabilis Dubey & Martin sp. nov. from Malaysia. New species descriptions are accompanied with camera lucida drawings and microphotographs of holotype and paratypes. Tuberaleyrodes actinodaphnis Takahashi is elevated from its status as a variety of T. machili Takahashi to species level. Lectotypes are selected for T. actinodaphnis Takahashi Stat. nov. and T. bobuae Takahashi. Tuberaleyrodes actinodaphnis Takahashi is a new record to Taiwan. A new combination, Tuberaleyrodes glutae (Corbett) Comb. nov. is proposed for Dialeurodes glutae Corbett. Two species, T. glutae (Corbett) and Tuberaleyrodes spiniferosa (Corbett) are re-described, and placement of T. spiniferosa in the genus Tuberaleyrodes is confirmed. The genus Tuberaleyrodes is newly recorded from Borneo and Sulawesi. An identification key to puparia of Tuberaleyrodes species so far described is provided along with the countries of present records. Four plants families viz., Annonaceae, Fabaceae, Myristicaceae and Pentaphylacaeae are recorded as new hosts for Tuberaleyrodes species. New host plant records are indicated.